A FALCO Zrt. hulladékkezelési logisztikája - Kovácsné Szakács Eszter (2015)
In my thesis I work out the details of waste management areas by analysing the company FALCO Ltd. in order to makesuggestionsrelated to the development of the waste management system. Although I did not spend my internship at FALCO Ltd, I chose this company, because in my opinion amongst woodworking companies they represent the kind of waste management that had awoken my interest. An appropriate waste management is important in many ways. Nowadays there are more and more raw materials needed, however, if waste is collected and recycled adequately, less raw materials will be necessary and the resources will last longer. Another aspect is that if waste is not handled and stored appropriately, it will pollute the environment immensely. The essence of environmentally conscious thinking is that we do not have to eliminate waste, but conduct waste management. With this we mean deliberate activities, such as prevention, elimination and minimization of waste emergence. At first some key points are defined with the help of the available technical literature, which are used henceforth. I make a general presentation of FALCO Ltd with headquarters in Szombathely, in which I show the business environment of the company as well. I show the analysis of the company’s strategy by using SWOT evaluation, which includes the strengths, weaknesses, risks and opportunities of the company. I analyse the company based on Porter’s 5-factor-model as well. By using PEST evaluation I analysed the impact of environmental factors. In my thesis I explain the main values of FALCO Ltd as well as the certificates and the products of the company, emphasizing the area of waste management. Within the area of waste management I introduce the arrangement of waste management, the different types of incurred waste at FALCO Ltd and I describe the collection, storage and expedition of waste emerging during fabrication and production. Before making any suggestions I also deal with the takeover of external waste, where I describe the takeover procedure at the company. In the last chapter I made suggestions concerning waste management system of the evaluated company according to which the incurredash and fly-ash should be stored in a container with a higher volume. As a result of this the transport costs could be decreased, the transport would take shorter time and, last but not least, it would also be beneficiary for the environment. I also make a suggestion concerning the storage of packaging waste. As for the storage of packaging waste, I suggest that the company should try to compress these materials. With this procedure the company could save time and money.